The sia particle in colloquial Singapore English - Khoo, Velda Yuan Ling. (2012)
The study of utterance particles in Singapore Colloquial English (SCE), or more commonly known as Singlish, is traditionally known as one fraught with difficulties, mainly due to the problems of pinning down exact grammatical functions and interactional motivations for this unique word class. This paper studies a relatively new particle in the SCE lexicon sia, within the Conversation Analysis framework. Unlike the more common particles in SCE like lah, leh, lor etc. that have since become identifying elements of the language itself, sia is a more socially marked particle used by a smaller subset of SCE speakers. Through the analysis of extracts from naturally occurring data, this paper aims to 1) determine the interactional function of sia and 2) find the relationship between markedness of the particle and how sia is used in interaction. It is found that the main functions of sia is relational, as it helps speakers mark and establish an in-group relationship with interlocutors they identify as ‘fellow sia users’ and in conversation itself, define a moment in time where interaction goes one level deeper by appealing to this relationship between speakers. By naming sial, a colloquial Malay swear word, as one of the most probable sources of the paper sia in SCE, the paper also examines how the negative connotations of sial might have influenced who uses sia and in the ways mentioned above. The study of sia shows us that the SCE speaker community could be more structurally complex than just the traditional socio-educational divisions into acrolectal, mesolectal and basilectal speakers. It highlights how speakers use elements in the language to construct their own identity, create participant categories and then act upon these identities as they define relationships with the people around them. This dynamic, intuitive process, then, proves that the speakers cannot be ‘divided’ in the traditional sense and only through the analysis of talk-in-interaction can we satisfyingly reflect these relationships between the speakers in the community.